The Effectiveness Of Using Podcasts In Improving Students’ Listening Skill At SMP N 3 Tareran - Wijaya, Oey; Lambe, Livianni; Pelenkahu, Noldy (Program Studi Pendidikan Bahasa Inggris, 2025)
This research is about the effectiveness of podcasts to improve the listening skills of 8th grade students at SMPN 3 Tareran. The objective of this study is to find out the effectiveness of podcasts in improving students’ listening skill at SMPN 3 Tareran. A pre-experimental one-group pretest-posttest design was implemented with 14 students as participants. This research used listening test before and after treatment using podcast media that focused on daily activities. Data were analyzed using a paired samples T-Test on IBM SPSS 30, by contrasting the results of the pre-test and post-test. The mean post-test score (75.0000) was considerably higher than the pre-test score (37.8571), demonstrating that students' listening abilities have significantly improved. The paired sample t-test resulted in a p-value of <0.001, which is under the significance threshold of 0.05, revealed statistically significant difference. Based on these findings, H0 is rejected and H1 is accepted, which confirms that podcasts are a useful resource for enhancing students listening skills by providing accessible and engaging learning materials.